2023
DOI: 10.26879/1241
|View full text |Cite
|
Sign up to set email alerts
|

Late Pleistocene and Holocene pikas (Mammalia, Lagomorpha) from Europe and the validity of Ochotona spelaea: New insights based on mtDNA analysis

Abstract: Pikas were among small mammals that inhabited mammoth steppes during the last glacial. The evolutionary history of ochotonids in Europe is relatively well studied, although the taxonomic status of many described forms remains ambiguous, and the majority of extant species of the genus Ochotona are poorly represented in the fossil record. The present study aims to analyse the taxonomic relationships of a sample of Late Pleistocene-Holocene pikas based on mtDNA data and to clarify the status of the species descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 61 publications
(92 reference statements)
0
0
0
Order By: Relevance
“…The measurements also do not significantly differ from O. pusilla spelea (Table 4). Research has shown a rather wide intraspecific variability of O. pusilla during the Pleistocene for its representatives dispersed over vast steppe and mountainous areas of Europe (Rabiniak et al, 2023). Thus, from the LAC Ia material, an attribution to a subspecies level is not possible.…”
Section: Ochotonidaementioning
confidence: 99%
“…The measurements also do not significantly differ from O. pusilla spelea (Table 4). Research has shown a rather wide intraspecific variability of O. pusilla during the Pleistocene for its representatives dispersed over vast steppe and mountainous areas of Europe (Rabiniak et al, 2023). Thus, from the LAC Ia material, an attribution to a subspecies level is not possible.…”
Section: Ochotonidaementioning
confidence: 99%